2001
DOI: 10.1038/sj.mp.4000784
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and localisation within a linkage hotspot of Disrupted In Schizophrenia 1, a gene disrupted by a translocation segregating with schizophrenia

Abstract: Two overlapping and antiparallel genes on chromosome 1, Disrupted In Schizophrenia 1 and 2 (DISC1 and DISC2), are disrupted by a (1;11)(q42.1;q14.3) translocation which segregates with schizophrenia through at least four generations of a large Scottish family. Consequently, these genes are worthy of further investigation as candidate genes potentially involved in the aetiology of major psychiatric illness. We have constructed a contiguous clone map of PACs and cosmids extending across at least 400 kb of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
121
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 17 publications
0
121
0
Order By: Relevance
“…The translocation disrupts a gene termed disrupted-in-schizophrenia 1 (DISC1) on chromosome 1. 5,7,9 Linkage and association at the DISC1 locus have been demonstrated for psychiatric illness in several populations, [10][11][12][13][14][15][16][17] suggesting wider relevance of DISC1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The translocation disrupts a gene termed disrupted-in-schizophrenia 1 (DISC1) on chromosome 1. 5,7,9 Linkage and association at the DISC1 locus have been demonstrated for psychiatric illness in several populations, [10][11][12][13][14][15][16][17] suggesting wider relevance of DISC1.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 An alternative approach is to study families in which schizophrenia and allied psychiatric disorders segregate with cytogenetic abnormalities. 7 In these families, a single major genetic defect could confer susceptibility to psychiatric illnesses. One large Scottish pedigree was identified, 8 in which a balanced (1:11) (q42.1; q14.3) translocation co-segregates with major psychiatric disorders (LOD scores = 4-7).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The function of the DISC2 was presumed to be involved in the regulation of DISC1 expression. 4,5 Nevertheless, no gene was found to be disrupted at the break point in chromosome 11q14.3.…”
mentioning
confidence: 99%
“…On the opposite strand, the translocation falls in the middle of DISC2, an apparently untranslated gene that has no known function. 5,8 Other genetic studies have indicated that factors at the DISC1 locus may contribute to the risk of psychiatric disorders. Linkage 9,10 and association 11 of schizophrenia to 1q42 has been reported in Finnish populations, and linkage was also detected in a Taiwanese population.…”
mentioning
confidence: 99%
“…Further, as a translocation, it is difficult to exclude the possibility of effects at the other locus of translocation (11q14.3), although genes have not been identified at this location. 5,8 It also remains possible that the translocation could influence other genes in the vicinity of DISC1 27 or that disruption of DISC2 could be of etiologic significance. Given these uncertainties, identification of additional DISC1 mutations that segregate with schizophrenia would substantially strengthen the case that DISC1 is an important factor in at least some cases of schizophrenia.…”
mentioning
confidence: 99%